Writ of Habeas Corpus Vis a Vis Mental Health Patients : An Analysis - Ishita Sharma (Indian Journal of Forensic Medicine & Toxicology, 2021)
Habeas corpus, as a writ has generally been associated with illegal incarceration of individuals. It is a writ,which is considered as an epitome of all remedies as far as implementation of human rights is concerned.Recently, the usage of the writ has surpassed the dimensions of technicalities of procedure of illegal detentionand entered into more intricate aspects of an individual’s life. Consequently, with the passage of time, the writassumed varied dimensions, , one among them being the usage of the writ in relation to individuals sufferingfrom mental health issues, for instance, where the individual is being denied the freedom of movement,occupation and exercising the freedom of choice .Apart from the political domain, the use of the writ has crept into facets of family laws, public laws. Theresearcher shall deal with the outreach of the writ in matters of health law. There has been very scantresearch in the outreach of the reach in aspects transcending political scenarios, owing to the fact that thereexist explicit legislations on such issues and exploring the possibility of the use of the same in the abovementioned arena has been rarely considered. The researcher has recommended an invigorated use of the writapart from illegal incarceration of prisoners through an analysis of several cases on this aspect.